2012
DOI: 10.1002/nbm.2832
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl sulfoxide (DMSO) as a potential contrast agent for brain tumors

Abstract: Dimethyl sulfoxide (DMSO) is commonly used in preclinical studies of animal models of high‐grade glioma as a solvent for chemotherapeutic agents. A strong DMSO signal was detected by single‐voxel MRS in the brain of three C57BL/6 control mice during a pilot study of DMSO tolerance after intragastric administration. This led us to investigate the accumulation and wash‐out kinetics of DMSO in both normal brain parenchyma (n = 3 control mice) by single‐voxel MRS, and in 12 GL261 glioblastomas (GBMs) by single‐vox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…DMSO crosses the blood brain barrier and can diffuse through cellular membranes (29). A previous study also reported a strong resonance seen at 2.7 ppm and suggested the use of DMSO as a potential contrast agent for brain tumors (30). This solvent is very efficient as a delivery mechanism for CNO, however care must be taken in the spectral analysis to avoid inaccurate results in the metabolites of interest.…”
Section: Resultsmentioning
confidence: 78%
“…DMSO crosses the blood brain barrier and can diffuse through cellular membranes (29). A previous study also reported a strong resonance seen at 2.7 ppm and suggested the use of DMSO as a potential contrast agent for brain tumors (30). This solvent is very efficient as a delivery mechanism for CNO, however care must be taken in the spectral analysis to avoid inaccurate results in the metabolites of interest.…”
Section: Resultsmentioning
confidence: 78%
“…First, a genetically engineered mouse (GEM, S100-v-ErbB; Ink4a-Arf(+/-)), female, age 40 weeks, bearing a Schwannoma (confirmed by histopathological studies carried out by Dr. Martí Pumarola, Murine Pathology Unit, Centre de Biotecnologia Animal i Teràpia Gènica, UAB ). Animals from this colony generally develop oligodendrogliomas [53], although a small percentage of animals can develop other tumour types [54]. The second model studied was a mouse bearing a stereotactically-induced GL261 glioblastoma, described elsewhere [55,56], age 20 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…SV spectra were acquired at short and long echo time. Tumour-bearing mice were also studied by PE-MRSI with DMSO [21] and/ or with glucose under mild hypothermia [22,23]. Bloodbrain barrier (BBB) integrity was evaluated with gadoterate meglumine (DOTAREM, Guerbet, Roissy, F rance) using contrast-enhanced (CE) T 1W images.…”
Section: Mr Studiesmentioning
confidence: 99%
“…c Color-coded intensity map representing the relative DMSO signal (as described in [21]) detected at 66 min after its i.p. administration.…”
Section: Disaggregated Tumour Model Using Cdt From Gl261mentioning
confidence: 99%
See 1 more Smart Citation